Information seeking behaviour of electronic records management systems (ERMS) users: implications for records management practices. - Singh, Pauline; Klobas, J.; Anderson, K. (University College of Bors, 2007)
This article considers whether the way RM professionals manage records in accordance with the ISO 15489 standard is consistent with the information seeking behaviour (ISB) of Electronic Records Management Systems (ERMS) users. The empirical research includes an investigation of the ISB of ERMS users and how various factors, such as training, individual information seeking styles, tasks, and time, affect the ISB. Forty ERMS users in four Australian government organisations ? in the utility, town council, banking and finance industries ? participated in the study. Qualitative research methods (interviews and protocol analysis) were used to develop a model of the ISB of ERMS users. An understanding of how ISO 15489 was implemented in the ERMSs of the organisations was obtained from interviews with the organisations? records managers. The findings reveal that there is a partial match between the ISB of ERMS users and how the organisations implemented the ISO 15489 standard to manage records in the ERMSs. Users rely heavily on using the metadata elements included in the ERMSs. They are mostly happy with their ability to find records in the ERMSs, but they encounter difficulties and frustration when performing some searches. These searches could be completed more efficiently and effectively if users had a better understanding of the classification scheme or thesaurus, but records managers do not generally make these tools available to the users.